PENGEMBANGAN BAHAN AJAR TEKS DRAMA BERDASARKAN PENGALAMAN PENGARANG - Didin Khaerudin; Suherli Kusmana; Iyay Robia Khaerudin (Program Studi Pendidikan Bahasa Indonesia Pascasarjana UGJ, 2019)
Research conducted to develop drama text teaching materials based on the experience of the author of the drama script aims to make it easier for students to understand drama text material. In addition, based on the author's experience students are expected to emulate the author's creative process in writing a paper. The research method used in this research is the research and development method. Based on the results of the interview it can be concluded that the ability to write drama is determined based on mastery of the elements of drama and the ability to develop stories based on the author's experience. The process of writing drama is done in several steps: (1) searching for ideas based on personal experience, other people, or the surrounding environment; (2) processing ideas to find plots (characters), characters or characters that vary with their inner conflicts, settings and dialogues, interesting conflicts, and messages to be conveyed; (3) starts the process of writing drama with stages and elements of drama; (4) revision of drama products. Teaching material developed is presented from basic competencies of knowledge and basic competencies of learning skills. Based on experiments on developed teaching materials it is known that the average value of the ability to write plays gets a score exceeding the minimum criteria, so that the teaching materials used are effective. Based on observations it is known that teaching materials can help students in learning and student activities become more independent, and active.